The impact of agri-food supply channels on the efficiency and links in supply chains - Zhanarys Raimbekov; B. U. Syzdykbaeva; Aigerim Rakhmetulina; Zhibek Rakhmetulina; Tana Abylaikhanova; Mainur Ordabayeva; Lyubov Doltes (Economies, 2023)
Improving the efficiency in the links in the supply chains of agri-food products is relevant in terms of the assessment methodology and practical aspects for ensuring and supporting sustainable supply chains of products not only in individual channels of product movement but also in the end-to-end supply chain of products, i.e., from the field to the end consumer. However, it is still unclear which supply chain opportunities in commodity distribution channels are more effective for creating end-to-end sustainable supply chains for agri-food products. The purpose of the study is to develop a methodology for assessing the impact of agri-food supply channels on the efficiency and link in supply chains, taking into account the factors affecting them and developing recommendations for their improvement. Quantitative methods based on correlation and regression analysis using the EViews program on the basis of Kazakh statistical data for 2008-2022 were used. A methodology is proposed for assessing the effectiveness of the functioning and links in commodity movement in the supply chains of agricultural products at the macroeconomic level based on the consideration and use of important factors affecting the efficiency and links: production and sales volumes, total costs, and profitability for each supply channel: 'production-processing-industrial production-trade'. The relationship between the efficiency and the links in supply chains and also the key factors that affect them have been established. The results showed that the increase in the efficiency in supply channels in the commodity distribution system leads to a decrease in the coefficient of the link in commodity movement and inventory availability. To reduce the link ratio in the supply chains of agri-food products, it is necessary to increase the efficiency in supply chains in each supply chain link and reduce the share of retail trade in the gross turnover. Recommendations are proposed to improve supply chain efficiency and reduce links to support and create end-to-end sustainable supply chains of agri-food products. The study makes an essential contribution to providing empirical evidence of the relationship between the effectiveness of agri-food supply channels and the link in the supply chain. Since few works describe the relationship between the links of product distribution and the efficiency in supply chains in the literature, in this work, it was possible to propose a methodology and identify factors and gaps in research to identify potential areas for future research.
Keywords: 330; agri-food supply chain; connectivity ratio; distribution channels; economic sustainability; goods flow; profitability; supply chain performance; trade